2020
DOI: 10.1108/sasbe-03-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort prediction by applying supervised machine learning in green sidewalks of Tehran

Abstract: PurposeThis research aims to introduce a new methodology for integration between urban design strategies and supervised machine learning (SML) method – by applying both energy engineering modeling (evaluating phase) for the existing green sidewalks and statistical energy modeling (predicting phase) for the new ones – to offer algorithms that help to catch the optimum morphology of green sidewalks, in case of high quality of the outdoor thermal comfort and less errors in results.Design/methodology/approachThe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In this process, studies have validated that the usage of environmentalist sidewalks could optimize the quality of life within urban spaces (Eslamirad et al , 2020). On the other hand, studies suggested that walking and cycling can be considered as the most environmentally friendly types of transportation in terms of facilitating sustainable urban mobility (Nourian et al , 2018).…”
Section: Research Findingsmentioning
confidence: 99%
“…In this process, studies have validated that the usage of environmentalist sidewalks could optimize the quality of life within urban spaces (Eslamirad et al , 2020). On the other hand, studies suggested that walking and cycling can be considered as the most environmentally friendly types of transportation in terms of facilitating sustainable urban mobility (Nourian et al , 2018).…”
Section: Research Findingsmentioning
confidence: 99%
“…Quality control capability (QCC) is considered an essential component of a manufacturing unit (Cica et al, 2020 ; Eslamirad et al, 2020 ; Rana et al, 2020 ). Silbernagel et al ( 2020 ) said that QCC is a process by which manufacturing firms can assess and review factors involved in a manufacturing firm’s production quality.…”
Section: Theoretical Background and Development Of Conceptual Modelmentioning
confidence: 99%
“…Figure 7a illustrates the percentage of input parameters used in MLTC studies. Architectural and building parameters were elucidated in only 2 studies [118,129].…”
Section: Choosing Features For Prediction Modelsmentioning
confidence: 99%